Analisis Faktor-Faktor Yang Mempengaruhi Surplus Underwriting Asuransi Umum Syariah Di Indonesia - Febrinda Eka Damayanti; Imron Mawardi (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
The purpose of this research is to know whether factors of Surplus Underwriting (participant contributions, claims and investment returns) have significant effect, both simultaneously and partially. The method used in this research is quantitative method and also using the secondary data which obtained from financial reports and other reports started from 2012 – 2014. The population is sharia general insurance and sharia unit of general insurance in Indonesia. The sample are 13 general insurance companies that comply with the spesified sample criteria. Analysis technique used is multiple linier regression analysis of panel data.